APG Marketing & Management Sdn Bhd / Muhammad Naqib Izzuddin Abdul Rahim - Abdul Rahim, Muhammad Naqib Izzuddin (Faculty of Business and Management, 2023)
Internship at APG Marketing & Management Sdn Bhd was a valuable and enriching experience that provided me with a wide range of knowledge and skills in marketing and including creating posters, engaging in telemarketing, and designing recruitment materials. These experiences allowed me to showcase my creativity, communication abilities, and problem-solving skills, which are essential in the real estate industry. One of the highlights of my internship was visiting a showhouse, where I gained practical insights into the real estate field by observing how managers interacted with customers and provided consultations. This experience instilled in me a sense of maturity, bravery, and determination to excel in the sales process. I am grateful for the guidance and support provided by Advisor George Dage and the entire team at APG. Their mentorship played a crucial role in my professional development, and I appreciate the opportunities they provided me to learn and grow. In analysing the SWOT analysis, I recognize that APG has several strengths, including its market connections and networks, problem-solving skills, and marketing capabilities. However, it also faces challenges such as high competition among employees and limited geographic reach. To capitalize on opportunities and mitigate threats, I recommend that APG focus on fostering a collaborative work environment to deal with competition, expand its marketing efforts to reach a wider audience, and diversify its service offerings to reduce dependence on a single geographic market. Furthermore, addressing cybersecurity threats and implementing robust security measures will help protect customer data and build trust among clients. Additionally, conducting regular cyber security training for employees will enhance their awareness and preparedness to tackle potential cyber threats. Overall, my training internship at APG was a transformative experience that deepened my passion for the real estate industry and equipped me with valuable skills for future endeavours. I am excited to continue building on the knowledge gained during my internship and applying it to further excel in the dynamic field of marketing and property promotion.